Mediation in the law governing administrative courts in Spain (Acta Judicial Journal, 2020)
This article was initially intended to analyse the situation of mediation in the Jurisdicción Contencioso-administrativa (Law governing Administrative Courts) in Spain, inviting the reader to reflect on the need to promote mediation in this area of the legal system, a need that has become more pressing following the new reality arising from the COVID-19.Previously, a study was developed regarding the basic principles of mediation, its peculiarities in this jurisdictional order, the evolution that the tool has experienced in our legal system as well as the advantages and difficulties that it offers. Finally, we identify some conflicts that have been found in mediation the best way to manage and solve them.Throughout the presentation, reference will be made to the role that the Letrado de la Administracion de Justicia (judicial officer) occupies and should occupy in the benefit of both the Administration of Justice and the citizen, the ultimate recipient of the functions entrusted to him, without forgetting that, in any case, collaborative and coordinated work is the key to any organization.We are aware of the achievements made by mediation in this jurisdictional order, as well as the road ahead.
Keywords: Mediation, collaborative work, participation, effective legal protection, justice, COVID- 19